WAYS TO INCREASE THE ECONOMIC EFFICIENCY OF FRUITS AND VEGETABLES COOPERATIVES IN UZBEKISTAN - Sobirova , Markhabo (THE INNOVATION ECONOMY, 2023)
this article presents the need to organize fruit and vegetable cooperations in the development of Agriculture and increasing the efficiency of the sphere in Uzbekistan. Measures for the organization and sustainable development of fruit and vegetable cooperation are presented.